Carcinoembryonic antigen‐related cell adhesion molecule 1 controls IL‐2‐dependent regulatory T‐cell induction in immune‐mediated hepatitis in mice. Issue 1 (14th May 2018) - Horst, Andrea Kristina; Wegscheid, Claudia; Schaefers, Christoph; Schiller, Birgit; Neumann, Katrin; Lunemann, Sebastian; Langeneckert, Annika E.; Oldhafer, Karl J.; Weiler‐Normann, Christina; Lang, Karl S.; Singer, Bernhard B.; Altfeld, Marcus; et al.
Abstract : A dysbalance between effector T cells (Tconv) and regulatory T cells (Tregs) and impaired Treg function can cause autoimmune liver disease. Therefore, it is important to identify molecular mechanisms that control Treg homeostasis. Carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1; CD66a) is an immune coreceptor with dichotomous roles in T‐cell regulation: its short isoform (CEACAM1S) can activate T cells and induce Tregs, whereas its long isoform (CEACAM1L), containing two intracellular immune receptor tyrosine‐based inhibitory motifs, can inhibit activated T‐cell function. In the liver, CEACAM1 has antifibrotic effects in models of nonalcoholic steatohepatitis. However, its role in immune‐mediated hepatitis is unknown. In the mouse model of concanavalin A–induced CD4 + T‐cell‐dependent liver injury, liver damage was aggravated and persisted in Ceacam1 −/− mice. Concomitantly, we observed hyperexpansion of Tconv, but reduction of interleukin (IL)‐2 production and hepatic forkhead box protein P3 + (Foxp3 + )CD4 + Treg numbers. CEACAM1 −/− CD4 + T cells showed impaired IL‐2‐mediated signal transducer and activator of transcription 5 (STAT5) phosphorylation, which correlated with a failure of naïve CEACAM1 −/− CD4 + T cells to convert into Tregs in vitro . Furthermore, CEACAM1 −/− Tregs expressed reduced levels of Foxp3, CD25, and B‐cell lymphoma 2. Adoptive transfer experiments demonstrated that hepatic Treg expansion and suppressive activity required CEACAM1 expression on both CD4 + T cells and Tregs. We identified predominant CEACAM1S expression on hepatic CD4 + T cells and Tregs from mice with acute liver injury and expression of both isoforms in liver‐derived CD4 + T‐cell clones from patients with liver injury. Conclusion : Our data suggest that CEACAM1S expression in CD4 + T cells augments IL‐2 production and STAT5 phosphorylation leading to enhanced Treg induction and stability, which, ultimately, confers protection from T‐cell‐mediated liver injury. (Hepatology 2018;68:200‐214).